A New Species of Brachycephalus from the Atlantic Rain Forest in São Paulo State, Southeastern Brazil (Amphibia: Anura: Brachycephalidae) - Haddad, Celio Fernando Baptista [UNESP]; Alves, Ana Claudia R. [UNESP]; Clemente-Carvalho, Rute Beatriz G.; dos Reis, Sergio F. (Amer Soc Ichthyologists & Herpetologists, 2010)
We describe a new toadlet species of the genus Brachycephalus from the Atlantic rain forest in the State of São Paulo, in southeastern Brazil. Specimens were collected from the leaf litter at approximately 750 m above sea level. The new species differs from its congers by the following combination of characteristics: SVL in adult males 11.3-12.1 mm and SVL in adult females 13.4-14.2 mm, skin on head and dorsum with co-ossification, general color in life orange with dorsal greenish irregular markings covered with small dark spots and dots, skull hyperossified, spinal processes of sacral and pre-sacral vertebrae hyperossified, and hyperossification of the distal end of the process of the fourth vertebra. The new species shares with most other Brachycephalus species remarkable traits, such as miniaturization and hyperossification of the skeleton. The new species probably occurs in isolation in highlands of the Atlantic Forest.